Effect of mesoscopic pore structure on the leaching behavior of ion-adsorption rare earth ores - Yujun Luo; Guanshi Wang; Fuming Lin; Shili Hu; Jun Zhang; Wenjun Du (Hydrometallurgy, 2026)

Ultrasensitive and rapid detection of botulinum neurotoxin serotype A via Argonaute-mediated signal cascade with a pregnancy test strip readout - Weiling Yu; Yukang Chen; Shujie Zhang; Ruina Zheng; Zhanyin Lin; Yujun Mei; Qiancheng Zhan; Bowen Xue; Jinxuan Fan; Bo Liu; Song Gao; Yuan-Di Zhao; et al. (Food Chemistry, 2026)

A structure-constrained diffusion method for intelligent reinforcement design of bridge two-pile caps - Buyu Jia; Zhaofan Liang; Yujun Lin; Xiaolin Yu (Engineering Structures, 2026)

MOF-derived carbon composites: Magnetically induced high electromagnetic shielding effectiveness and intelligent regulation of absorption-dominated mechanism - Lin Chen; Yujun Rong; Xin Zhou; Xiyu Qiu; Xiaofan Ma; Shaohua Jiang; Jianzhong Guo (Chemical Engineering Journal, 2026)

A Multi-Model Ensemble Approach for Constructing Subseasonal Extreme Forecast Index of Temperature - Hong-Li Ren; Yujun Wang; Li Gao; Lin Wang; Minghong Liu; Yinghan Sang; Jieru Ma (Journal of Meteorological Research, 2026)

ε-poly-l-lysine–grafted nanocellulose prepared by enzymatic oxidation for high-internal-phase Pickering emulsions and nutraceutical delivery - Huangjingyi Chen; Yujun Zou; Chong Tang; Qingyang Lin; Jie Wu; Orlando J. Rojas; Yimin Fan (Carbohydrate Polymers, 2026)

Enhanced tolerance of triploid Betula pendula ‘Purple Rain’ to short-term chilling stress is associated with antioxidant capacity and BpSOD gene expression - Jie Zhang; Jingnan Li; Shicheng Li; Ling Lin; Long Liu; Xiaoyue Zhang; Ying Cui; Yujun Zhou; Jing Jiang (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Habitats guarded by terrain: The beneficial role of topographic heterogeneity in securing habitat quality - Lin Fang; Yujun Wang; Qiong Liu; Yanxiao Liu; Minghao Ou (Applied Geography, 2026)

Enrichment Characteristics of Normal-Pressure Marine Shale Gas in the Complex Tectonic Zone: A Case Study of the Lower Cambrian Niutitang Formation in Northern Guizhou - Wenjibin Sun; Zhonghu Wu; Yujun Zuo; Chao Pan; Hao Liu; Baofeng Lan; Jianyun Lin; Bin Chen; Qinggang Chen (Journal of Earth Science, 2026)

Nature-inspired bicontinuous-topology 3D-printed TPMS solar interfacial evaporator - Yifeng Liao; Yizhe Liu; Lin Ren; Yujun Wei; Zhijian Huang; Jing Zhang; Zhongxin Xu; Jianing Wu; Junyang Tao; Shudong Yu; Shuo Wu (Chemical Engineering Journal, 2026)

End-to-end intelligent rapid design method for bridge single-pile based on generative adversarial networks - Buyu Jia; Zhaofan Liang; Wentao Ou; Yujun Lin; Xiaolin Yu (Engineering Structures, 2026)

A New Shear Strength Model for Filled Discontinuities Based on the Disturbed State Concept Theory - Hang Lin; Hailong Bie; Zhanming Shi; Jiangteng Li; P. G. Ranjith; Yujun Zuo (Rock Mechanics and Rock Engineering, 2026)

Toward circular plastic economy: Conversion of marine waste PET into sustainable bio-based polyesters with carbon negative emissions - Hongtao Ning; Qian Ding; Qiang Zhang; Guiquan Liao; Yujun Chen; Qian Liu; Xiaoqiong Xie; Shimei Xu; Lin Chen; Yu-Zhong Wang; Bo Wu; Jianjun Li (Chemical Engineering Journal, 2026)

A novel approach to identify the spatial characteristics of ozone-precursor sensitivity based on interpretable machine learning - Huiling He; Kaihui Zhao; Zibing Yuan; Jin Shen; Yujun Lin; Shu Zhang; Menglei Wang; Anqi Wang; Puyu Lian (Journal of Environmental Sciences, 2026)

Long-term performance and optimization of two-phase closed thermosyphons for buried large-scale warm-oil pipelines under rising oil temperature - Wenyuan Lei; Yapeng Cao; Guoyu Li; Dong Li; Yujun Cui; Shaoqun Lin; Yan Zhang; Anshuang Su; Miao Wang; Xu Wang (Cold Regions Science and Technology, 2026)

A registration and construction quality analysis framework for low quality hull block point cloud with extensive redundant structures - Shilin Huo; Ji Wang; Rui Li; Yujun Liu; Lin Pang; Jian Zhang (Ocean Engineering, 2025)

Hydrodynamic force analysis of semi-submerged propeller and influence on shaft whirling vibrations - Fangshuai Wei; YuJun Liu; Ji Wang; Rui Li; Lin Pang (Ocean Engineering, 2025)

Permafrost degradation due to fire disturbance: A case study in the Da Xing’anling mountains, Northeastern China - Yapeng Cao; Guoyu Li; Wei Ma; Yujun Cui; Dun Chen; Kai Gao; Juncen Lin; Changqing Li; Anshuang Su (CATENA, 2025)

Single-electrode multiplex sensing via metal ion displacement method - Yiming Zhang; Zhi Chen; Songrui Wei; Huiling Lin; Yujun Zhang; Yingxia Liu; Jing Wang; Qi Gao; Defa Li; Han Zhang; Zhongjian Xie (Chemical Engineering Journal, 2025)

Unveiling a two-stage closed-pore formation mechanism in bamboo-derived hard carbons for high-plateau-capacity sodium-ion battery anodes - Zhenbing Sun; Zhenrui Li; Yujun Li; Zhihui Wang; Haifeng Zuo; Lin Zhao; Xinge Liu (Chemical Engineering Journal, 2025)

Subseasonal Extreme Forecast Index for High Temperature Based on the ECMWF S2S Model Data - Yujun Wang; Li Gao; Hong-Li Ren; Lin Wang (Journal of Meteorological Research, 2025)

Benzo(a)pyrene-loaded gypsum dust-induced apoptosis of human bronchial epithelial cells through the Ahr signaling pathway - Yujun Wang; Juan Song; Qingqing Lin; Zhenzhen Lv; Faqin Dong; Jianjun Deng (Molecular & Cellular Toxicology, 2025)

A Computational Study on the Excitation Forces of Partially Submerged Propellers for High-Speed Boats - Fangshuai Wei; Yujun Liu; Ji Wang; Rui Li; Lin Pang (Journal of Marine Science and Engineering, 2025)
During high-speed navigation, boat propellers often become partially exposed due to elevated sailing speeds. This condition results in a unique operational scenario where propellers are only partially submerged. Conducting computational studies on the excitation of propellers under such circumstances is essential for optimizing the dynamic performance of the shafting system. A theoretical calculation method for propeller performance was developed based on the principles of fluid dynamics relevant to water entry, leading to a computational method for determining excitation forces in this specific operational condition. This method was subsequently refined through appropriate adjustments using ANSYS Fluent software to simulate the behavior of partially submerged propellers. The findings highlighted the accuracy of the proposed model in predicting the pulsation of six force components across three distinct directions: along the propeller shaft, vertical, and lateral. Specifically, for a single blade (Blade 1), the pulsation amplitude of the vertical force (Fx) constituted 82.1% of its maximum peak magnitude and equated to 57.5% of the blade’s mean thrust. Analogously, the lateral force (Fz) pulsation amplitude represented 53.3% of its maximum peak magnitude and 40.0% of the mean thrust. These findings indicate the presence of significant unsteady hydrodynamic loads. Furthermore, a visualization approach was presented to analyze blade load phasing, offering insights relevant to the arrangement of blades on partially submerged propellers.

Research on the Forming Detection Technology of Shell Plates Based on Laser Scanning - Ji Wang; Baichen Wang; Yujun Liu; Rui Li; Shilin Huo; Jiawei Shi; Lin Pang (Journal of Marine Science and Engineering, 2025)
In order to solve the problems of low efficiency and insufficient accuracy of the traditional manual template method in the forming detection of shell plates, a digital solution based on laser scanning detection system was proposed. By introducing a six-degree-of-freedom robotic arm and a high-precision line laser sensor to build a three-dimensional detection platform, a digital template method framework including data acquisition, point cloud registration, surface reconstruction, and deviation analysis was innovatively constructed. A point cloud non-penetration registration algorithm fused with boundary geometric information was proposed. Based on the improved Delaunay triangulation algorithm, the surface is reconstructed and the digital template is extracted. Experimental verification shows that the method achieves an accuracy of less than 1 mm of error in the detection of outer plates, shortens the single detection time to less than 10 min, and improves the detection efficiency by more than 75% compared with the traditional method.

Stair-Stepping metamaterial and the derived isolator for all-DOF vibrations with multi-payloads - Haifeng Ou; Jia Zeng; Minqing Lin; Yifan Wang; Yujun Zeng; Xi Fang; Lingling Hu (Engineering Structures, 2025)

CRISPR CLAMP: Attomolar level of multiple miRNAs - Yiming Zhang; Zhi Chen; Songrui Wei; Jing Wang; Yujun Zhang; Huiling Lin; Hai Fu; Yingxia Liu; Qi Gao; Han Zhang; Zhongjian Xie (Chemical Engineering Journal, 2025)

An AP2/ERF transcription factor GhERF109 negatively regulates plant growth and development in cotton - Huiyun Shi; Ghulam Qanmber; Zuoren Yang; Yuling Guo; Shuya Ma; Sheng Shu; Yujun Li; Zhongxu Lin; Fuguang Li; Zhao Liu (Plant Science, 2025)

Higher Magnesium Depletion Score Increases the Risk of All-cause and Cardiovascular Mortality in Hypertension Participants - Jingjing Song; Yujun Zhang; ZhiGen Lin; Jiazhen Tang; Xiaorong Yang; Fang Liu (Biological Trace Element Research, 2025)

Establishment and application of novel transient cotyledon and seed transformation systems in Tartary buckwheat - Huala Wu; Hui Li; Jiayi Lin; Yujun Ouyang; Chenglei Li; Hongyou Li; Tao Wang; Qi Wu; Haixia Zhao (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Polycyclic aromatic hydrocarbons emissions from biomass-fueled boilers in China - Chunlin Zhang; Meixue Yang; Jiangyong Li; Hao Wang; Lin Song; Liran Shen; Li Bai; Yujun Lin; Jun Liu; Boguang Wang (Journal of Hazardous Materials, 2024)

A smart home energy management system based on human activity recognition and deep reinforcement learning - Zhouwen Wu; Xia Chen; Yujun Lin; Jinyu Wen; Yin Chen (Energy and Buildings, 2024)

Two-Level regulation photocatalytic activity of Bi2WO6/COFs with ligand engineering and piezoelectric field for Highly-Efficient degradation of antibiotics - Yujun Ju; Hailong Lin; Chen Chen; Ruien Hou; Zhe Wang; Tinglong Hao; Min Xu; Yu Tang; Fengjuan Chen (Chemical Engineering Journal, 2024)

Association Between the Serum Copper Levels and Environmental Tobacco Exposure on the Risk of Overweight and Obesity in Children: a Study Based on the National Health and Nutrition Examination Survey - Yujun Luo; Linzhu Zhang; Yanting Lu; Xiaohong Lin; Zelin Weng; Youjia Xu (Biological Trace Element Research, 2024)

Casein hydrolysate in naturally-fermented buckwheat sourdough: Effects on fermented and physicochemical characteristics, texture, and bacterial microbial composition - Ling Guo; Biqi Liu; Chen Liang; Wen Sun; Yujun Jiang; Xueqi Yun; Lin Lu; Xinhuai Zhao; Ning Xu (International Journal of Food Microbiology, 2024)

Characterization of a novel recombinant NADC30‑like porcine reproductive and respiratory syndrome virus in Shanxi Province, China - Jianle Ren; Shanshan Tan; Xinxin Chen; Xizhen Wang; Yiting Lin; Yi Jin; Sheng Niu; Ying Wang; Xiaolong Gao; Libin Liang; Junping Li; Yujun Zhao; et al. (Veterinary Research Communications, 2024)

Effects of exogenous steroid hormones on growth, body color, and gonadal development in the Opsariichthys bidens - Qingyuan Liu; Jinchun Hu; Yurui Lin; Xinrui Wu; Yujun Feng; Jiazheng Ye; Kai Zhang; Shanjian Zheng (Fish Physiology and Biochemistry, 2024)

Wide-swath and high-resolution whisk-broom imaging and on-orbit performance of SDGSAT-1 thermal infrared spectrometer - Zhuoyue Hu; Xiaoyan Li; Liyuan Li; Xiaofeng Su; Lin Yang; Yong Zhang; Xingjian Hu; Chun Lin; Yujun Tang; Jian Hao; Xiaojin Sun; Fansheng Chen (Remote Sensing of Environment, 2024)

Modulating the microenvironment of catalytic interface with functional groups for efficient photocatalytic degradation of persistent organic pollutants - Yujun Ju; Ze Wang; Hailong Lin; Ruien Hou; Hua Li; Zhe Wang; Ruitong Zhi; Xiaoquan Lu; Yu Tang; Fengjuan Chen (Chemical Engineering Journal, 2024)

Bavachin combined with epimedin B induce idiosyncratic liver injury under immunological stress conditions - Mengmeng Lin; Yingying Li; Bo Cao; Jing Xu; Yujun Zhang; Guohui Li; Xiaohe Xiao; Chunyu Li (Chemico-Biological Interactions, 2023)

Seamless Prediction in China: A Review - Hong-Li Ren; Qing Bao; Chenguang Zhou; Jie Wu; Li Gao; Lin Wang; Jieru Ma; Yao Tang; Yangke Liu; Yujun Wang; Zuosen Zhao (Advances in Atmospheric Sciences, 2023)

Biodegradation of polylactic acid by a mesophilic bacteria Bacillus safensis - Yujun Wang; Ting Hu; Wanting Zhang; Jinwei Lin; Zhanyong Wang; Shuxia Lyu; Haibin Tong (Chemosphere, 2023)

Development and application of DETECTR-based rapid detection for pathogenic Bacillus anthracis - Jianhao Xu; Xinru Bai; Xianglilan Zhang; Bing Yuan; Lei lin; Yan Guo; Yujun Cui; Jinxiong Liu; Hongyu Cui; Xiangang Ren; Jinglin Wang; Yuan Yuan (Analytica Chimica Acta, 2023)

Combination of highly photovoltaic and highly transparent materials enables record performance semitransparent organic solar cells - Lin Zhao; Xuexiang Huang; Yukai Wang; Sang Young Jeong; Bin Huang; Jiawei Deng; Jiabin Liu; Yujun Cheng; Han Young Woo; Feiyan Wu; Limin Chen; Lie Chen (Chemical Engineering Journal, 2023)

Research status, challenges and future prospects of renewable synthetic fuel catalysts for CO2 photocatalytic reduction conversion - Yujun Chen; Bin Guan; Xingze Wu; Jiangfeng Guo; Zeren Ma; Jinhe Zhang; Xing Jiang; Shibo Bao; Yiyan Cao; Chengdong Yin; Di Ai; Yuxuan Chen; et al. (Environmental Science and Pollution Research, 2022)

Mesoscopic damage evolution characteristics of sandstone with original defects based on micro-ct image and fractal theory - Yujun Zuo; Zhibin Hao; Hao Liu; Chao Pan; Jianyun Lin; Zehua Zhu; Wenjibin Sun; Ziqi Liu (Arabian Journal of Geosciences, 2022)

A new DRP-4DVar-based coupled data assimilation system for decadal predictions using a fast online localization technique - Yujun He; Bin Wang; Wenyu Huang; Shiming Xu; Yong Wang; Li Liu; Lijuan Li; Juanjuan Liu; Yongqiang Yu; Yanluan Lin; Xiaomeng Huang; Yiran Peng (Climate Dynamics, 2020)

An integrated strategy to identify genes responsible for sesquiterpene biosynthesis in turmeric - Jingru Sun; Guanghong Cui; Xiaohui Ma; Zhilai Zhan; Ying Ma; Zhongqiu Teng; Wei Gao; Yanan Wang; Tong Chen; Changjiangsheng Lai; Yujun Zhao; Jinfu Tang; et al. (Plant Molecular Biology, 2019)

Diversity and evolution of Lactobacillus casei group isolated from fermented dairy products in Tibet - Jing Feng; Yujun Jiang; Mingyu Li; Siyu Zhao; Yanming Zhang; Xuesong Li; Hui Wang; Guangen Lin; Hao Wang; Tiejing Li; Chaoxin Man (Archives of Microbiology, 2018)

Evaluation of Immunosuppressive Activity of Demethylzeylasteral in a Beagle Dog Kidney Transplantation Model - Huimin An; Yu Zhu; Wenping Xu; Yujun Liu; Jianping Zhang; Zongming Lin (Cell Biochemistry and Biophysics, 2015)

Risk Evaluation of Selective Renal Arterial Embolization in the Treatment of Delayed Hemorrhage from Renal Artery Pseudoaneurysm After Partial Nephrectomy - Yu Zhu; Yujun Liu; Jianping Zhang; Zongming Lin (Cell Biochemistry and Biophysics, 2014)